TEN DAYS TRAINING EFECTIVITY ON MEASURED SPECIFIC MOTOR ABILITIES OF BASKETBALL PLAYERS 15 YEARS OF AGE - Pavle Rubin (Sport Mont, 2009)
Research took place in the basketball camp “Kikinda 07”. The sample consisted of 20 basketball players, 15 years of age (cadets), from Kikindas basketball clubs. On the inicial (9.VIII 2007. year) and final (19.VIII 2007. year) measurement, 9 tests spe- cific motor abilities (SMA) were done: Player movement with the ball, Ball manipulation and Player movement without the ball. The aim was to prove 10 days training efektivity (15 trainings at 90 min.) on specific motor abilities (SMA) at cadets. Basketball players (cadets) were trained under programme made by author of this research. The differences between two measurements (initial and final) were proven using multivariate analysis of variance (MANOVA). Using this results the significant statistical difference appeared between two measuremeents (on .00 level). Univariate analysis of variance (ANOVA) proved a statistical significant better results after training (in final measurement) in 4 tests (variable): “Kamikaze” (shorted) with driving (on .05 level); Driving the ball aro- und central circle (on .00 level) (for SMA measurement movement player with a ball); and for SMA ball manipulation: Driblling with variations and Circling with ball around a body (on .00 level).